Artificial Intelligence and the Future of Journalism: Risks and Opportunities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Artificial Intelligence (AI) has become an increasingly prominent subject, drawing public interest and leading to a rise in both scholarly research and media attention. This article explores how AI is portrayed in journalistic contexts by the media in Brazil and Portugal, along with the challenges it introduces. Nonetheless, issues such as misinformation, ethical concerns, and potential threats to journalistic integrity received relatively little attention. The analysis highlighted major themes such as AI’s dual nature as both beneficial and potentially harmful, the necessity for human oversight, and the difficulties media organizations face in adapting to these changes. Overall, the study indicates that the media in Brazil and Portugal tend to frame AI as a beneficial development for journalism, while often minimizing its risks and ethical dilemmas.